ETR300 Fundamentals of Entrepreneurship. Business Plan : Big Boys Toys / Haessler Symphoon Paul... [et.al] - Paul, Haessler Symphoon; Grunsin, Micheal Kadong; Kalang, Janet; Seddek, Ezzah Syafiqah; Hasbi, Mohd Raahdiq; Bunsu, Muhd Nurkamil (2011)
The name of our company is Big Boy Toy car accessories. The business is in form of enterprise which consists of six members. Each partner contributes certain amount of capital as agreed in agreement. Our business operation is at 8am-5pm on weekdays only. There are no sleeping partners and all are entitled to participate in the business management. We agreed that Haessler Symphoon Anak Paul is our General Manager, Ezzah Syafiqah Binti Seddek and Janet Kalang as the Adminitration Manager, Mohammad Raadiq Bin Hasbi is the Operational Manager, Micheal Kadong Anak Grunsin as Financial Manager and Muhammad Nurkamil Bin Bunsu as marketing Manager. The selection of General Manager is based on consensus among all the partners and selected based on the experience, skills and ability. The management team will be led by the General Manager and assist by the other managers. The General Manager is responsible for the job that related to administration such as planning and arranging the remuneration schedule of salary and wages. The Operation Manager is responsible to the entire job that related to the operation and will be supervise and coordinate the operation of the business. The Marketing Manager will be responsible to create the market plan, identifying the customer’s need and demand, identifying the competitors, target market, market size and forecast the future market. Lastly, the Financial Manager will be handled the financial matters such as preparing the budget and financial statement for expenses of each departments and controlling the flow of the money of the organization.